Experimental characterization and modelling of the elastic properties of direct compounded compression molded carbon fibre/polyamide 6 long fibre thermoplastic. (15th May 2017) - Bondy, Matthew; Pinter, Pascal; Altenhof, William
Abstract: Characterization of 9% to 25% weight fraction compression molded carbon fibre LFT-D polyamide-6 was completed with orientations of 0°, ± 45°, and 90°. A key finding is that tensile stiffness/strength and flexural stiffness were higher in the + 45° direction compared to − 45° (tensile modulus: 20%, strength: 10%, flexural modulus: 8%). Correspondingly, engineering strain at failure for uniaxial tensile tests was 18% lower in the + 45° direction. This is hypothesized to be the result of fibre orientation asymmetry in the compression molding charge. Fibre orientation was measured by CT, fibre length was measured by matrix incineration/optical microscopy, and micromechanics models were employed to model elastic characteristics. An effectiveness was established for each process configuration by comparing the experimental modulus to the Generalized Self Consistent model. For the 0° direction, this effectiveness is approximately 90%. However, fibre length is more critical for the specimen geometry studied in the ± 45° and 90° directions and this effectiveness is much lower (approximately 70%). Measurements of fibre length by an industrial partner without experience with direct compounding yielded data, that when input into the micromechanics models, poorly predicted mechanical characteristics for 0°. A length measurement methodology yielding accurate data is critical in modelling basic mechanical properties. Graphical abstract: Highlights: Characterization of compression molded carbon fibre polyamide-6 subjected to uniaxial tension and three point bending Tensile stiffness/strength and flexural stiffness were higher in the + 45° direction with respect to -45° Micromechanics /fibre orientation and length data estimates of the tensile modulus with a percent error of approximately 22%